Effective Personal Tax Rates on Marginal Skills Investments in OECD Countries A New Methodology - Brys, Bert (OECD Taxation Working Papers, 2013)
This paper presents a new methodology to calculate effective tax rates on the marginal return on an investment in skills within a discounted cash-flow investment framework. This approach takes into account costs including forgone labour earnings and the direct costs of skills formation, as well as the earnings premium and the return of an alternative investment in capital income. The earnings premium necessary to pursue a skills investment is calculated endogenously. This framework can be used to analyse the financial incentives to invest in skills and the impact of different policies for financing post-secondary education and/or professional training. The paper looks in particular at the effects of personal taxes (possibly net of benefits received) on incentives to acquire skills by estimating the effective tax rate on the return on a marginal skill investment - that is, one where the resulting increase in earnings is just enough to make the investment financially worthwhile; this "margin" can span multiple years. This approach may be helpful to policymakers in assessing the impact of tax progressivity and/ or the withdrawal of benefits and the case for tax breaks for postsecondary education and training, and could be extended to compare the impact of tax breaks relative to other policy instruments to stimulate skills investments. The paper includes some illustrative calculations in order to demonstrate how to apply the methodology within the OECD's Taxing Wages framework for all OECD countries, which is left for follow-up work